A Novel Grape-Derived Prebiotic Selectively Enhances Abundance and Metabolic Activity of Butyrate-Producing Bacteria in Faecal Samples - Oliver, Lia; Ramió-Pujol, Sara; Amoedo, Joan; Malagón, Marta; Serrano, Marta; Bahí, Anna; Lluansí, Aleix; Torrealba, Leyanira; Busquets, David; Pardo, Laura; Serra-Pagès, Mariona; Aldeguer, Xavier; et al. (Frontiers in Microbiology, 2021)
Inflammatory Bowel Disease (IBD) and Irritable Bowel Syndrome (IBS) patients have different faecal microbiota profiles compared to healthy controls. Prebiotics intake influences intestinal microbiota composition which in turn influence the growth of short-chain fatty acids (SCFA) producing bacteria. This study aimed to evaluate the capacity of Previpect, a new prebiotic obtained from grapes fibre, to balance the dysbiosis found in patients with intestinal disorders. This was achieved through the analysis of specific bacterial markers and SCFA production using an in vitro fermentation system and comparing the obtained results with those obtained with other commercial prebiotics. Fresh faecal samples from patients with IBD (N=6), IBS (N=3), and control subjects (N=6) were used. Previpect showed high fermentative ability enabling the growth of butyrate producing bacteria and increasing SCFA concentration up to 2.5-fold. Previpect is a promising prebiotic which may be used as a therapeutic strategy towards promotion of intestinal microbiota restoration, microbial healing, and as a preventive supplement for healthy individuals.